Culture of Chaetoceros calcitrans as Natural Feed for Mytilopsis adamsi Cultivation at National Research and Innovation Agency, North Lombok - At'tamimi, Muhamad Ridho Ilham; Diniariwisan, Damai (Journal of Fish Health, 2025)
This study was conducted to explore the culture technique of Chaetoceros calcitrans as a natural feed and its role in supporting the maintenance of the brown mussel (Mytilopsis adamsi). The microalga was chosen because it provides essential nutrients such as proteins, lipids, and carbohydrates that are important for the growth of aquatic organisms. The work took place over one month, from May 6 to June 4, 2025, at the National Research and Innovation Agency (BRIN), North Lombok. The culture followed a stepwise approach, starting with sterilization of equipment and media, the addition of KW21 fertilizer and silicate, inoculation with five-day-old seed cultures, daily maintenance, and cell density monitoring. The observations showed that C. calcitrans density rose steadily from the first day and peaked on day 5 at 4,020,000 cells/ml, before declining by day 7. This trend reflects the typical growth phases of microalgae, from lag and exponential to stationary and death phases. Feeding trials involved offering C. calcitrans to brown mussels twice daily at a dose of 500 ml each time. The results indicated consistent weight gain across all replicates, although growth levels varied among treatments. Overall, the study confirms that stepwise culture with appropriate nutrient supply and water quality management can produce C. calcitrans at optimal densities. Its application as a natural feed also provides measurable benefits for the growth of brown mussels in culture systems.